A Study Of Economic Evaluation Of The Development Of Small -Scale Industries By Dic Intervention (Journal of Namibian Studies : History Politics Culture, 2023)
In developing nations, small-scale industries (SSIs) play an essential role in creating jobs, reducing poverty, and fostering regional growth. This is especially true in emerging economies. Established as nodal agency, District Industries Centres (DICs) in India provide financial aid, skill development, technical support, and market access efforts to SSIs, ensuring their growth and sustainability. Examining the effects on industrial growth, entrepreneurship, and socio-economic change, this research offers an economic assessment of DIC interventions in promoting the development of SSIs. The study shows that DIC programs help SSIs with issues including lack of funding, old technology, and poor infrastructure, and it also finds ways to make DIC programs better by improving their outreach and execution. The full potential of these interventions is hindered by discrepancies in budget allocation and program implementation, notwithstanding their important benefits. In order to get the most of DIC programs, this study stresses the necessity of better legislative measures, more money, public-private collaborations, and sustainable methods. The long-term survival and competitiveness of SSIs may be ensured by DICs via the building of institutional frameworks and the use of innovative techniques. This, in turn, can contribute to equitable and sustainable economic growth.